Randomized Multicenter Trial Comparing Glue Fixation, Self-gripping Mesh, and Suture Fixation of Mesh in Lichtenstein Hernia Repair (FinnMesh Study). Issue 5 (November 2015) - Rönkä, Kirsi; Vironen, Jaana; Kössi, Jyrki; Hulmi, Tanja; Silvasti, Seppo; Hakala, Tapio; Ilves, Imre; Song, Indrek; Hertsi, Merja; Juvonen, Petri; Paajanen, Hannu
Abstract : Objective: Three different mesh fixation techniques were compared to find out how to perform a safe and cost-effective open inguinal hernioplasty in day-case setting with the best outcomes with regard to chronic pain. Summary Background Data: Mesh fixation method may influence on the incidence of chronic pain after Lichtenstein hernioplasty. Methods: Lichtenstein hernioplasty was performed under local anesthesia in 625 patients as day-case surgery in 8 Finnish hospitals. The patients were randomized to receive either a cyanoacrylate glue (Histoacryl, n = 216), self-gripping mesh (Parietex ProGrip, n = 202), or conventional nonabsorbable sutures (Prolene 2-0, n = 207) for mesh fixation. The incidence of wound complications, pain, recurrences, and patients discomfort was recorded on days 1, 7, 30, and 1 year after surgery. The primary endpoint was the sensation of pain measured by pain scores and the need of analgesics after 1 year of surgery. Results: The type and size of inguinal hernias were similar in the 3 study groups. The duration of operation was 34 ± 13, 32 ± 9, and 38 ± 9 minutes in the glue, self-gripping, and suture groups, respectively ( P  < 0.001). There were no significant differences postoperatively in pain response or need for analgesics between the study groups. Two superficial infections (0.3%), 31 wound seromas (5.0%), and 4 recurrent hernias (0.6%) were recorded during a 1-year follow-up. Some 25 patients (4.2%) needed occasionally analgesics for chronic groin pain. A feeling of a foreign object and quality of life were similar in all study groups. Conclusions: This randomized trial failed to prove that mesh fixation without sutures causes less inguinodynia than suture fixation in Lichtenstein hernioplasty. Mesh fixation without sutures is feasible without compromising postoperative outcome.